Worrying about wasting GP time as a barrier to help-seeking: a community-based, qualitative study - Cromme, SK; Whitaker, KL; Winstanley, K; Renzi, C; Smith, CF; Wardle, J (Royal College of General Practitioners, 2016)
Background: Worrying about wasting GP time is frequently cited as a barrier to help-seeking for cancer symptoms. Aim: To explore the circumstances under which individuals feel that they are wasting GP time. Design and setting: Community-based, qualitative interview studies that took place in London, the South East and the North West of England. Method: Interviewees (n = 62) were recruited from a sample (n = 2042) of adults aged ≥50 years, who completed a ‘health survey’ that included a list of cancer ‘alarm’ symptoms. Individuals who reported symptoms at baseline that were still present at the 3-month follow-up (n = 271), and who had also consented to be contacted (n = 215), constituted the pool of people invited for interview. Analyses focused on accounts of worrying about wasting GP time. Results: Participants were worried about wasting GP time when time constraints were visible, while dismissive interactions with their GP induced a worry of unnecessary help-seeking. Many felt that symptoms that were not persistent, worsening, or life-threatening did not warrant GP attention. Additionally, patients considered it time-wasting when they perceived attention from nurses or pharmacists to be sufficient, or when appointment structures (for example, ‘one issue per visit’) were not adhered to. Close relationships with GPs eased worries about time-wasting, while some patients saw GPs as fulfilling a service financed by taxpayers. Conclusion: Worrying about wasting GP time is a complex barrier to help-seeking. GP time and resource scarcity, symptom gravity, appointment etiquette, and previous GP interactions contribute to increasing worries. Friendly GP relationships, economic reasoning, and a focus on the GP’s responsibilities as a medical professional reduce this worry.